Why Is the Public Sector More Labor-Intensive? : A Distortionary Tax Argument - Panu Poutvaara; Andreas Wagener (Institute for the Study of Labor (IZA), 2004)
Government-run entities are often more labor-intensive than private companies, even with identical production technologies. This need not imply slack in the public sector, but may be a rational response to its wage tax advantage over private firms. A tax-favored treatment of public production precludes production efficiency. It reduces welfare when labor supply is constant. With an elastic labor supply, a wage tax advantage of the public sector may improve welfare if it allows for a higher net wage. This would counteract the distortion of labor supply arising from wage taxation. Full privatization is never optimal if the labor supply elasticity is positive but small.
Keywords: L33; H21; D24; J45; 330; public sector; labor intensity; taxation; Öffentlicher Sektor; Arbeitsintensität; Lohnsteuer; Steuerbelastung; Theorie